Artefact appropriation in facilitated modelling: An adaptive structuration theory approach. Issue 11 (2nd November 2021) - Tavella, Elena; Papadopoulos, Thanos; Paroutis, Sotirios
Abstract: Scholars have long acknowledged the importance of unveiling the black box of Operational Research (OR) practice. However, despite the emerging empirical studies in the area known as "Behavioural OR", there is still a dearth of research into how artefacts are used at the micro-level of OR practice. This article addresses this gap by using adaptive structuration theory (AST) to study the appropriation (use) of artefacts during a facilitated modelling (FM) workshop. We argue that the appropriation of artefacts from the workshop participants enables them to engage in negotiation of meaning with action implications effectively, but appropriation occurs at varying intensities (high, medium, and low) depending on the issue of concern. Moreover, we identify that artefacts are reproduced if their reproduction is an aim or part of an aim of strategic discourse. Finally, we outline the limitations of our study and future research avenues.